2021
DOI: 10.3390/life11111198
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRi as a Tool to Repress Multiple Copies of Extracellular Polymeric Substances (EPS)-Related Genes in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: The use of the versatile cyanobacterial extracellular polymeric substances (EPS) for biotechnological/biomedical applications implies an extensive knowledge of their biosynthetic pathways to improve/control polymer production yields and characteristics. The multiple copies of EPS-related genes, scattered throughout cyanobacterial genomes, adds another layer of complexity, making these studies challenging and time-consuming. Usually, this issue would be tackled by generating deletion mutants, a process that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…CRISPRi has emerged as a strategy to selectively inhibit photosynthetic genes. CRISPRi enables a particularly intriguing strategy for manipulation of photosynthetic proteins due to its reversibility and its potential to multiplex targets through incorporation of multiple guide RNAs [ 126 , 127 ]. In one example of this type of strategy, DNase-dead Cpf1 was introduced into S. elongatus UTEX 2973 as part of a CRISPRi system to target Photosystem I for inhibition [ 128 ].…”
Section: Use Of Crispr and Crispr Interference For Study Of Photosynt...mentioning
confidence: 99%
“…CRISPRi has emerged as a strategy to selectively inhibit photosynthetic genes. CRISPRi enables a particularly intriguing strategy for manipulation of photosynthetic proteins due to its reversibility and its potential to multiplex targets through incorporation of multiple guide RNAs [ 126 , 127 ]. In one example of this type of strategy, DNase-dead Cpf1 was introduced into S. elongatus UTEX 2973 as part of a CRISPRi system to target Photosystem I for inhibition [ 128 ].…”
Section: Use Of Crispr and Crispr Interference For Study Of Photosynt...mentioning
confidence: 99%
“…Genes associated with nucleoside diphosphate saccharide production from the serine pathway were highly expressed in "M. sinica" at high nitrite input, providing materials for polymerization to EPS. 52 EPS is then secreted by the mechanism associated with increased expression of wza 53 and kpsM 54 providing a barrier from nitrite toxicity. 55 Similar genes are expressed at a low level (about 100−1000-fold less) in "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…sinica” at high nitrite input, providing materials for polymerization to EPS . EPS is then secreted by the mechanism associated with increased expression of wza and kpsM providing a barrier from nitrite toxicity . Similar genes are expressed at a low level (about 100–1000-fold less) in “ Ca.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the genetic manipulation of cyanobacteria has a significant effect on EPS production. Therefore, a number of investigations have been carried out to modify Cyanobacterial EPSs' characteristics and production [83][84][85]. However, our understanding of the genetic and enzymatic systems associated with EPS formation is still a very small portion of what has been derived from the complete mechanism.…”
Section: Cyanobacterial Epsmentioning
confidence: 99%